2014
DOI: 10.1016/j.cellsig.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active NDR1-PIF kinase functions independent of MST1 and hMOB1 signalling

Abstract: The human MST1/hMOB1/NDR1 tumour suppressor cascade regulates important cellular processes, such as centrosome duplication. hMOB1/NDR1 complex formation appears to be essential for NDR1 activation by autophosphorylation on Ser281 and hydrophobic motif (HM) phosphorylation at Thr444 by MST1. To dissect these mechanistic relationships in MST1/hMOB1/NDR signalling, we designed NDR1 variants carrying modifications that mimic HM phosphorylation and/or abolish hMOB1/NDR1 interactions. Significantly, the analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…To test whether STK38 signalling plays a role in this setting, we assessed the consequences of STK38 depletion using three different siRNAs (Figure 1) and overexpression of hyperactive STK38-PIF (Supplementary Figure S1). This revealed that HK-HT cells expressing oncogenic HRasG12V (henceforth called HK-HRasG12V) with transient STK38 depletion displayed significantly decreased soft agar colony formation (Figure 1A, 1B, 1C), while expression of hyperactive STK38-PIF [38] was not sufficient to transform HK-HT cells (Supplementary Figure S1). Although human STK38L (aka NDR2) is similar to human STK38 [26, 27], efficient STK38L depletion in HK-HRasG12V had no effect on anchorage-independent growth (Figure 1D, 1E, 1F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether STK38 signalling plays a role in this setting, we assessed the consequences of STK38 depletion using three different siRNAs (Figure 1) and overexpression of hyperactive STK38-PIF (Supplementary Figure S1). This revealed that HK-HT cells expressing oncogenic HRasG12V (henceforth called HK-HRasG12V) with transient STK38 depletion displayed significantly decreased soft agar colony formation (Figure 1A, 1B, 1C), while expression of hyperactive STK38-PIF [38] was not sufficient to transform HK-HT cells (Supplementary Figure S1). Although human STK38L (aka NDR2) is similar to human STK38 [26, 27], efficient STK38L depletion in HK-HRasG12V had no effect on anchorage-independent growth (Figure 1D, 1E, 1F).…”
Section: Resultsmentioning
confidence: 99%
“…Retroviral plasmids encodingHRasG12V, HRasG12V/E37G, HA-STK38 PIF, HA-STK38 PIF/kd, and shLUC have been reported [34, 38, 62]. To generate the pSuper.retro.puro_shSTK38-2 vector expressing shRNAs against human STK38, the following oligonucleotide pairs were inserted into pSuper.retro.puro (Oligoengine) using BglII and HindIII : 5′-GATCCCCGTCGGCCATAAACAGCTATTCAAGAGATAGCTGTTTATGGCCGACGTTTTTGGAAA-3′ and 5′- AGCTTTTCCAAAAACGTCGGCCATAAACAGCTATCTCTTGAATAGCTGTTTATGGCCGACGGG-3′ targeting the 3′UTR of STK38.…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of Tao-1 and TAO1 binding to GCKIII kinases was carried out in low-stringency buffer as defined previously (Cook et al, 2014). Anti-HA antibodies were from Cell Signaling (C29F4) and Roche (3F10).…”
Section: Star Methodsmentioning
confidence: 99%
“…To investigate whether STK38's kinase activity is required for its nuclear/cytoplasmic shuttling, HeLa cells were silenced for endogenous STK38 followed by transient expression of wild-type STK38 (wt), kinase-dead (K118R) [3], or constitutively active (PIF) STK38 [28]. Transfected cells were subsequently submitted to nutrient starvation and stained for STK38 subcellular localization ( Fig 3A and B).…”
Section: Stk38 Accumulates In the Cytoplasm Upon Nutrient Starvationimentioning
confidence: 99%